Antibacterial Activity of Lime Peel and Lemongrass Extract as Active Ingredients for Spray Hand Sanitizer - Djima, Elza Gitaa Eirene Djima; Prasetyaningsih, Aniek; Madyaningrana, Kukuh (Universitas Kristen Duta Wacana, 2021)
Hand sanitizers are widely used as an alternative way to maintain hand hygiene from the presence ofpathogenic bacteria, such as Staphylococcus aureus. In general, excessive use of alcohol as the main ingredientin hand sanitizers might cause skin irritation. Utilizing antibacterial activity of plants as a component in handsanitizer could be used as a substitution for alcohol. The aim of this study was to determine the potentialantibacterial activity of lime peel and lemongrass extracts as active ingredients for hand sanitizer. Methodused in this research included extraction using maceration, qualitative phytochemical test, antibacterialassay, and formulation of spray hand sanitizer and quality test of spray hand sanitizer. In this study alkaloid,flavonoid, saponin, tannin and terpenoid were found as phytochemical content of lime peel, while lemongrassextract contain fla vonoid, tanin, saponin and steroid. Compared to lemongrass extract, lime peel extract withconcentration 40%showed the optimum inhibition zone of S. aureus and chosen as active ingredient in sprayhand sanitizer formulation. Formulated spray hand sanitizer with lime peel extract was able to inhibit thegrowth of S. aureus bacteria on hand palm.